Brain-derived uroguanylin as a regulator of postprandial brown adipose tissue activation: a potential therapeutic approach for metabolic disorders - Habek, Nikola; Ratko, Martina; Sedmak, Dora; Banovac, Ivan; Crljen, Vladiana; Kordić, Milan; Radmilović, Marina; Škokić, Siniša; Tkalčić, Martina; Mažuranić, Anton; Bubalo, Pero; Škavić, Petar; et al. (Frontiers in Pharmacology, 2025)
BackgroundPreclinical and clinical research of insulin resistance and glucose homeostasis in metabolic disorders are essential. In this study, we aim to determine the expression of uroguanylin (UGN) in the mouse and human brain, its regulatory mechanisms, and its significance to patients with obesity and type 2 diabetes (T2D).MethodsUGN expression, regulation, and its correlation with feeding status and obesity in the mouse and human brain were analyzed at the mRNA level using RT-PCR, qPCR, and in situ hybridization and at the protein level using Western blot, ELISA, and immunohistochemistry. Brown adipose tissue (BAT) activity was measured using infrared thermography. The volume of interscapular brown adipose tissue in mice was assessed by magnetic resonance imaging.ResultsUGN was expressed in both the mouse and human brain, and its expression was regulated by feeding. In the human prefrontal cortex, UGN was expressed in several interneuron subpopulations across all cortical layers. In Brodmann area (BA) 10, prouroguanylin (proUGN) expression was not regulated by feeding in obesity, whereas this regulation still persisted in BA9. In mice, centrally applied UGN and its analog linaclotide, affecting the hypothalamus, induced both acute and chronic activation of BAT, which decreases the plasma glucose concentration. However, in obesity, proUGN expression was reduced in the human hypothalamus, suggesting reduced postprandial glucose consumption in BAT. Similarly, centrally applied analog of glucagon-like peptide 1 (GLP-1—liraglutide) affected proUGN expression and was associated with increased basal BAT activity but reduced BAT activation after a meal in patients with T2D receiving GLP-1 therapy.ConclusionPostprandial BAT activation is regulated by brain-derived UGN, which could serve as a novel therapeutic approach to enhance BAT activity in patients with obesity and T2D to improve postprandial glucose regulation.